PENGARUH BOBOT UMBI SEBAGAI BIBIT DAN NAUNGAN TERHADAP PERTUMBUHAN KELADI TIKUS {Thyponium flageliforme (Lodd.) Bl.} - Juhaeti, Titi (BERITA BIOLOGI, 2002)
Keladi tikus Thyponium flageliforme (Lodd.) Bl. is considered as a wild plant species, because it is not fully cultivated yet. However,now adays it is quite widely used even in its wild status, because it is reported to be traditionally used as cancer cure. Due to its potential uses by the people, there is a need to be developed by cultivation in order to fulfill the demand for raw materials, both for medication and planting materials in research activities. This research was conducted to study the behaviour of keladi tikus when bring to cultivation status. The research is divided into two parts i.e: a) the effect of bulb weight as planting material and 2) the effect of shading on the growth. The result sshowed that bulb weight is not significantly affected the growth. On the 10month after planting the parameter measured is not significantly different. Meanwhile, shading is significantly affected the plant growth. The best growth is achieved on 0% shading, but the growth on 50% shading is still good. The growth on 75% shading has significant decreased.